DETERMINAN MINAT GENERASI MILENIAL PADA PENGGUNAAN SISTEM PEMBAYARAN E-WALLET LAYANAN SYARIAH LINKAJA - Putri Ananda; Aminah Nuriyah (Journal of Sharia Economics, 2023)
Goal: This study aims to determine whether perceptions of usefulness, perceived convenience, perceptions of security, Islamic financial literacy simultaneously affect the interest in using the LinkAja Syariah Service e-wallet payment system. Method: In this study, researchers used a descriptive quantitative approach with sampling techniques, namely non-probability sampling by distributing questionnaires to 105 respondents in the Jabodetabek area. This research method is multiple linear regression analysis with an error rate of 5%. Fact/Findings: The results found in this study are (1) the perception of convenience does not affect the interest in using LinkAja Syariah Services. (2) the perception of usefulness has a positive and significant effect on interest in using LinkAja Syariah Services. (3) the perception of security does not affect the interest in using the LinkAja Syariah Service. (4) Islamic Financial Literacy has a positive and significant impact on interest in using LinkAja's Syariah Services. (5) Perception of convenience, perception of usefulness, perception of security and Islamic financial literacy simultaneously have a positive and significant effect on interest in using LinkAja Syariah Services Keywords : Payment system, e-wallet, perceived ease of use, perceived ease of usefulness, perceived ease of security, Islamic financial literacy, intention to using